Application of a proposed TLS model in a lean productive system - Dias, Rui M. F. (2019)
The current market, becoming more rigid, forces companies to search continuously for innovation and improvement of their processes and products as a way to keep competitive and gain strategic advantages. Due to the global economic crisis, more and more companies try an approach through new management methodologies that allow better performances in terms of earning, profit and cost reduction. The present article proposes an integrated TOC (Theory of Constraints), Lean and Six-Sigma (TLS) model, with the objective of improving continuously a productive system, although it shows flexibility to be applied in other kinds of systems. The model synergistically integrate the best practices found in existing TOC, Lean and Six-Sigma models. The proposed model derivatives mainly from Eliyahu Goldratt's TOC model of the "5 focus steps" and TLS model "Ultimate Improvement Cycle", developed by Bob Sproull. The proposed TLS model was tested on an important Portuguese Manufacture. The implementation of a first continuous improvement cycle was completed and a second cycle began. The main results obtained by the implementation of the TLS model were extremely satisfactory.